Mapping and Inventorying Semi-arid Silvopastoral Systems - Louhaichi, Mounir; Hassan, Sawsan; Ouled Belgacem, Azaiez (International Center for Agricultural Research in the Dry Areas, 2024)
This report presented the Capacity Development Workshop on Mapping and Inventorying Semi-arid Silvopastoral Systems, conducted by ICARDA in May 2024. The workshop aimed to equip early-career professionals and students with foundational skills in geoinformatics and monitoring tools essential for managing semi-arid silvopastoral systems. Participants engaged in hands-on training using tools like VegMeasure and Google Earth, enhancing their ability to assess vegetation cover, estimate carrying capacity, and develop sustainable land-use strategies. The course emphasized the importance of silvopastoral systems in promoting environmental health and economic stability in semi-arid regions, addressing challenges such as land degradation and climate change. Feedback indicated high satisfaction levels, with significant knowledge improvement demonstrated through pre- and post-test evaluations.